Evaluation of accommodative function in the dominant and non dominant eye - Odigie, Oseleonomhen M.; Uwagboe, Precious N.; Okpaghoro, Omawumi P. (International Journal of Research in Medical Sciences, 2019)
Background: Ocular dominance is the physiological preference of one eye over the other, hence its input is favoured when there is conflicting information to the two eyes. Accommodation is the mechanism by which the eye changes focus from distant to near images and is produced by a change in the shape of the crystalline lens. The aim of this study was to compare the accommodative amplitude, facility and lag in the dominant and non-dominant eye. Methods: This cross sectional study was carried out on 80 visually normal subjects. Ocular dominance was determined using hole-in-the- card method. Amplitude of accommodation, accommodative facility and response was measured monocularly and randomly using push up method, ±2.00DS flipper lenses and Nott technique respectively. Results: Results obtained from the study showed that the right eye was dominant in 62.5% of subjects. The mean (SD) for accommodative amplitude, facility and response (lag) in the dominant eye was 11.08 (2.16) D, 10.00 (1.52) cycles per minute and 0.62 (0.27) respectively. The mean (SD) for accommodative amplitude, facility and lag in the non-dominant eye was 10.98 (2.20) D, 9.86 (1.44) cycles per minute and 0.60 (0.25) D respectively. Conclusions: It may be inferred that the dominant eye has more accommodative amplitude, facility and lag than the non-dominant eye but this difference was not statistically significant.